INDONESIAN FISHERIES AND SPICES COMMODITIES IN THE UNITED STATES AND THE EUROPEAN UNION: RSCA AND URR ANALYSIS - Sukarniati, Lestari; Rahmi, Mustika (Universitas Tidar, 2024)
Although Indonesia has potential in fisheries and spice commodities, Indonesia also faces challenges where food commodities including fisheries and Indonesian spices often experience rejection, especially from the United States and the European Union. On the other hand, with its potential, Indonesian fisheries and spices products are expected to have comparative advantages that result in improved quality of goods and services so as to provide higher competitiveness in international trade. This study aims to determine how the competitiveness and trade conditions of fishery commodities and spices from Indonesia to the United States and the European Union from 2015-2022. The analytical tools used in this study are Revelaed Symetric Comparative Advantage (RSCA) and Trade Specialization index (ISP) to analyze competitiveness while to analyze the reasons for rejection and its relation to the food quality of these commodities the Unit Rejection Rate (URR) analysis is used. From the research results, it was found that all Indonesian fishery and spice products traded to the United States and the European Union have a comparative advantage both in 2015 and in 2022 because they have an RSCA score above 0. While the URR value of Indonesian fishery and spice commodities to the United States and the European Union has also decreased, which means that the number of rejections is decreasing, and the quality of food quality is increasing.